Adaptation to climate change — Challenges for society, economy and state - Hecht, Dieter (Raumforschung und Raumordnung | Spatial Research and Planning, 2009)
Climate change cannot be avoided entirely. Hence, there is a need for actions to cope with a changing climate. In contrast to the avoidance of greenhouse gases households, firms and other owners of resources are self-interested in the adaptation to the consequences of climate change. Some kind of governmental or EU actions are justified by e.g. insufficient information, biased discounting of future costs and inappropriate incentives. As the uncertain impacts of climate change will differ regionally, rules and instruments should allow freedom of choice to those affected by climate change. A one-size-fits-all approach will clearly not be appropriate.